Bifunctinoal Phosphonium Salt‐Catalyzed Asymmetric Cyclodearomatization of 2‐Nitroindoles and 2‐Nitrobenzofurans for Constructing CF3‐Containing Spiro‐Polycycles. Issue 12 (23rd April 2021) - Jiang, Zhiyu; Liu, Xin; Zhang, Hongkui; Tan, Jian‐Ping; Ren, Xiaoyu; Gao, Guowei; Wang, Tianli
Abstract: An efficient enantioselective dearomative cycloaddition reaction between either 2‐nitroindoles or 2‐nitrobenzofurans and N ‐2, 2, 2‐trifluoroethylisatin ketimines by dipeptided phosphonium salt catalysis is firstly established. This protocol provides a new and facile synthetic approach to create a variety of CF3 ‐containing polycyclic spirooxindole derivatives under mild reaction conditions with high yields in excellent diastereo‐ and enantioselectivities (all >20:1 dr, up to 95% ee). Abstract :